FED FUND RATE DAN FLUKTUASI HARGA MINYAK: SEBUAH PENGUJIAN HERDING BEHAVIOR PADA PASAR SAHAM SYARIAH INDONESIA - Syafrina, Adelia Dwi; Ningtyas, Mega Noerman (RISTANSI: Riset Akuntansi, 2025)
With a focus on the Jakarta Islamic Index (JII), this study attempts to analyze how herding behavior is affected by changes in the Fed Fund Rate (FFR) and the oil price in the Indonesian Sharia stock market from 2019 to 2024. The sampling technique was purposive, by selecting 15 companies that were consistently included in the JII throughout the study period. Daily data was analyzed using regression method to identify the relationship between these variables and herding behaviour, which was measured using Cross-Sectional Absolute Deviation (CSAD). The results show that FFR significantly drives the herding behaviour phenomenon, where an increase in FFR tends to trigger an increase in herding in the Islamic stock market. In contrast, oil price fluctuations do not encourage the phenomenon of herding behaviour. This study concludes that US monetary policy through FFR is an important external factor influencing investor behaviour in Indonesia's Islamic stock market. However, the influence of oil prices tends to be more complex and requires further study